First Results of Monitoring the New Invasive Species Prunus serotina Ehrh. Population inside the Regeneration Area of Common Oak-Hornbeam Forest in Western Croatia - Medak, Jasnica (Array, 2021)
Black cherry (Prunus serotina Ehrh., Rosaceae) is a widespread invader of the European temperate forests and a significant component of the human-caused part of the global environmental changes. Its successful invasion results from a complex interaction between the species life traits and the recipient ecosystem attributes. While it has been recorded to develop spontaneously in numerous European countries, in Croatia information details on its population distribution, as well as its current status, are still missing. The individuals of P. serotina were found in the pedunculate oak (Quercus robur L.) forest regeneration area of Jastrebarsko forest management unit in 2018. This alerted us to start to monitor its spreading area, status and impact on the native plant species in a four-year period (2018-2021). In order to investigate the habitat characteristics, phytosociological approach was applied. In addition, the area was surveyed using an unmanned aerial vehicle (UAV) DJI Mavic 2 Pro and DJI Ground Station Pro. The results showed that P. serotina spread considerably in the regeneration area, which indicates its invasive character. It also caused alteration in current vegetation. Fast initial expansion of P. serotina in 2019 was slowed down in the next 2 years due to performed tending activities, suggesting mechanical measures could help to control its invasive spreading at an early stage of development. This research brought up the first record of the Prunus serotina species in pedunculate oak forest regeneration area of western Croatia with a recommendation to continue the monitoring survey in order to help prevent its spread in the future.